Independent Association of Lipoprotein(a) and Coronary Artery Calcification With Atherosclerotic Cardiovascular Risk - Mehta, Anurag; Vasquez, Nestor; Ayers, Colby R; Patel, Jaideep; Hooda, Ananya; Khera, Amit; Blumenthal, Roger S; Shapiro, Michael D; Rodriguez, Carlos J; Tsai, Michael Y; Sperling, Laurence S; Virani, Salim S; et al. (Journal of the American College of Cardiology, 2022)
Elevated lipoprotein(a) [Lp(a)] and coronary artery calcium (CAC) score are individually associated with increased atherosclerotic cardiovascular disease (ASCVD) risk but have not been studied in combination. This study sought to investigate the independent and joint association of Lp(a) and CAC with ASCVD risk. Plasma Lp(a) and CAC were measured at enrollment among asymptomatic participants of the MESA (Multi-Ethnic Study of Atherosclerosis) (n = 4,512) and DHS (Dallas Heart Study) (n = 2,078) cohorts. Elevated Lp(a) was defined as the highest race-specific quintile, and 3 CAC score categories were studied (0, 1-99, and ≥100). Associations of Lp(a) and CAC with ASCVD risk were evaluated using risk factor-adjusted Cox regression models. Among MESA participants (61.9 years of age, 52.5% women, 36.8% White, 29.3% Black, 22.2% Hispanic, and 11.7% Chinese), 476 incident ASCVD events were observed during 13.2 years of follow-up. Elevated Lp(a) and CAC score (1-99 and ≥100) were independently associated with ASCVD risk (HR: 1.29; 95% CI: 1.04-1.61; HR: 1.68; 95% CI: 1.30-2.16; and HR: 2.66; 95% CI: 2.07-3.43, respectively), and Lp(a)-by-CAC interaction was not noted. Compared with participants with nonelevated Lp(a) and CAC = 0, those with elevated Lp(a) and CAC ≥100 were at the highest risk (HR: 4.71; 95% CI: 3.01-7.40), and those with elevated Lp(a) and CAC = 0 were at a similar risk (HR: 1.31; 95% CI: 0.73-2.35). Similar findings were observed when guideline-recommended Lp(a) and CAC thresholds were considered, and findings were replicated in the DHS. Lp(a) and CAC are independently associated with ASCVD risk and may be useful concurrently for guiding primary prevention therapy decisions.